Psychmeta: An R Package for Psychometric Meta-Analysis. Issue 5 (July 2019) - Dahlke, Jeffrey A.; Wiernik, Brenton M.
Over the past four decades, psychometric meta-analysis (PMA) has emerged a key way that psychological disciplines build cumulative scientific knowledge. Despite the importance and popularity of PMA, software implementing the method has tended to be closed-source, inflexible, limited in terms of the psychometric corrections available, cumbersome to use for complex analyses, and/or costly. To overcome these limitations, we created the psychmeta R package: a free, open-source, comprehensive program for PMA.